(untitled) (Innovaciones Educativas, 2021)
This article/editorial is a reflection about the lessons learned from the COVID-19 crisis and how we can incorporate what we have learned as part of our efforts to adjust and improve our schools through educational policies. While returning to school after lockdown, instead of going back to “normal,” we emphasize the need to transform that “normal.” The pandemics evidenced that making some changes is possible. Those changes will be analyzed and described as a unique opportunity to redesign and reinvent schools.